Pengetahuan ahli keluarga terhadap penjagaan pesakit posoperatif di Hospital Universiti Sains Malaysia - Izrin Farhana, Jini
Introduction: Information and understanding about postoperative care is important to ensure patient's family readiness to face the problem. It can also ensure patient's family well-prepared to cooperate with the nurses during postoperative care. Objective: To study the level of knowledge in postoperative patient's care. Researcher also assessed relationship between degree of education with level of family's knowledge to deliver care to postoperative patient. Metodology: This is a cross-sectional study. Sample was represented by 64 family's postoperative patient in 3 surgery wards: 2 Intan, 3 Utara and I Utara. Level of knowledge was assessed by total mean score based on self-construct questions adapted from the book written by Harkness, A. G. & Dincher, R.J., 1996 titled Medical-Surgical Nursing- Total Patient Care, 9th edition. The choice of answers are 'yes' or 'no'. Researcher also study the relationship between level of knowledge by using One-way Analysis ofVariance(ANOVA) test. Result: Sixty eight point eight percent (68.8%) from respondents have high level of knowledge in postoperative patient's care. Degree of education shows that statistically significant with level of knowledge in postoperative patient's care.Conclusion : Level of family knowledge in postoperative patient's care shows the high prevalence and degree of education related with level of knowledge in accepting perioperative and postoperative education.